Effects of labour and credit market frictions on shock propagation, allocation, and recoveries - Schnattinger, P (2021)
This thesis contains three papers studying the consequences of labour and credit market frictions on the efficient allocation of resources and business cycle dynamics. A common theme of the three papers is that they focus on markets, where some market elements can be captured well with search frictions. The first paper estimates the extent to which aggregate job creation is driven by non-fundamental noise rather than fundamental news shocks employing maximum likelihood estimation of a DSGE model with search and matching in the labour market. The paper finds noise to play no role in aggregate job creation. Motivated by survey data on income growth expectations and labour market flow data, the second paper develops a mechanism where the information acquisition about idiosyncratic match quality is pro-cyclical. The mechanism, which is integrated into a directed search dynamic block recursive equilibrium model allows for a parsimonious explanation of observed survey data, labour market transition rates and finds counter-cyclical labour market mismatch. The third paper finds that the share of non-performing bank loans in total bank loans can be viewed as a mirror image of capital misallocation in many developed countries. The model developed from this observation shows that search frictions in used capital markets may drive non-performing, as will forbearance incentives. The paper estimates the extent to which changes in forbearance incentives and in the efficiency of used capital were responsible for variation in the share of non-performing loans. The introduction and conclusion of the thesis explain common themes and point to further applications of the content in the papers.